Pancreatic Islet Cell Transplantation: A new era in transplantation - Warnock, Garth L. (1992)
Transplantation of insulin-producing tissue offers a physiologic approach to restoration of glycemic control. Whereas transplantation of vascularized pancreatic grafts has recently achieved encouraging results, pancreatic islet cell transplantation holds the promise of low morbidity and reduced requirements for agressive immunosuppression for recipients. Islet cell transplantation was recently demonstrated to induce euglycemia with insulin independence.